Effect of pH and Gas Flow Rate on Ozone Mass Transfer of Κ-Carrageenan Solution in Bubble Column Reactor - Aji Prasetyaningrum; Dyah Arum Kusumaningtyas; Purbo Suseno; Ratnawati Ratnawati (Reaktor, 2018)
This research was conducted to calculate the mass transfer coefficient value for ozonation reaction of κ-carrageenan solution in the bubble column reactor. Ozone gas was produced using ozone generator type corona discharge. In this study, operating conditions were regulated at ozone gas flow rate 2- 5 L min-1, pH 4-10, and temperature 29 ± 1 oC. Samples were tested every 5 minutes to determine the dissolved ozone concentration. The results showed that dissolved ozone concentrations increased with increasing ozonation time and ozone gas flow rate. However, a very high gas flow rate can increase turbulence so that the mass transfer coefficient (kLa) value decreased. In alkaline conditions, the formation of free radicals (HO*) increases so that the amount of dissolved ozone decreases. The kLa value of ozone gas in κ-carrageenan solution is slightly lower than the kLa value of the ozone gas in the water. The results of this study indicate that (kLa) ozone gas in water is 0.131 / minute while the value (kLa) in κ-carrageenan solution is 0.128 / minute.Keywords: ozone; mass transfer; pH; flowrate